Building Resilient and Sustainable Built Environments Through Climate Adaptation, Digital Innovation, and Infrastructure Governance - Berawi, Mohammed Ali; Sari, Mustika; Miraj, Perdana (CSID Journal of Infrastructure Development, 2026)
The built environment has become one of the most important arenas for responding to climate change, resource pressure, and rapid urban transformation. Cities, infrastructure networks, buildings, and construction projects are no longer expected only to provide physical services. They are also expected to reduce environmental impact, protect communities from disruption, support economic activity, and remain useful under uncertain future conditions. This expectation places resilience and sustainability at the center of infrastructure development. Resilience refers to the capacity of built systems to anticipate shocks, absorb pressure, recover from damage, and continue functioning. Sustainability asks whether those systems can do so while using resources responsibly, reducing emissions, and supporting social wellbeing over the long term. Both concepts are strongly connected, but they are not interchangeable. A drainage system may reduce flood exposure but still fail as a sustainable solution if it ignores land use change, ecological function, or maintenance capacity. A new material may reduce cement consumption but cannot be adopted widely unless its strength, durability, safety, and economic value are demonstrated. In this sense, resilient and sustainable development is not only a matter of better design. It is a matter of how knowledge, institutions, technology, finance, and human capacity are brought together. Digital innovation has expanded what can be measured and managed in the built environment. Weather radar, drone photogrammetry, geospatial platforms, smart city applications, sensor networks, hydraulic modelling, Building Information Modelling, and enterprise resource planning systems allow engineers, planners, governments, and contractors to see risks and project conditions with greater detail. These tools can improve decision making, support coordination, and make infrastructure performance more transparent. However, technology does not remove the need for judgement. Rainfall radar still needs calibration. Flood dashboards still need reliable sensors and inclusive access. Enterprise systems still need capable users. Smart city platforms still need institutions that can respond to the information they receive. This is why infrastructure governance has become inseparable from climate adaptation. Better data will not reduce risk if planning systems cannot act on it. Digital platforms will not create resilience if they remain disconnected from land use control, investment priorities, public participation, and maintenance systems. Safety plans will not protect workers if they are not supported by budget allocation, supervision, and organizational discipline. Sustainable construction will not advance if new materials remain outside standards, procurement systems, and professional practice. Climate adaptation therefore depends not only on technical solutions, but also on the ability of institutions and project actors to translate evidence into action. The current challenge for the built environment is not a lack of innovation. Many promising tools and methods already exist. The larger challenge is whether these innovations can be made reliable, inclusive, affordable, and useful in real contexts. Resilient and sustainable built environments will emerge when digital tools strengthen governance, when sustainability claims are supported by technical evidence, when project management includes long term risk, and when communities are considered not only as beneficiaries but also as users of infrastructure systems.